2016
DOI: 10.1371/journal.pone.0161958
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Sjögrens Syndrome in Patients with Chronic Hepatitis Virus Infection: A Population-Based Analysis

Abstract: ObjectiveThe association between Sjögren’s syndrome (SS) and chronic hepatitis virus infection is inconclusive. Hepatitis B (HBV) and hepatitis C virus (HCV) infections are highly prevalent in Taiwan. We used a population-based case-control study to evaluate the associations between SS and HBV and HCV infections.Materials and MethodsWe identified 9,629 SS patients without other concomitant autoimmune diseases and 38,516 sex- and age-matched controls without SS from the Taiwan National Health Insurance claims d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
1
21
1
Order By: Relevance
“…However, the pathogenesis of the association between SS and HCV is not fully known and whether the sicca syndrome in patients with HCV is due to pSS, secondary SS or only SS-like symptoms remains controversial. 18 Moreover, neither correcting HCV in the multivariate Cox model nor the analysis after excluding patients with pSS with prior HCV and their matched controls resulted in different outcome. Thus, the initial study design was not altered and HCV was not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenesis of the association between SS and HCV is not fully known and whether the sicca syndrome in patients with HCV is due to pSS, secondary SS or only SS-like symptoms remains controversial. 18 Moreover, neither correcting HCV in the multivariate Cox model nor the analysis after excluding patients with pSS with prior HCV and their matched controls resulted in different outcome. Thus, the initial study design was not altered and HCV was not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic infection by the hepatitis C virus (HCV) is known to induce a number of extrahepatic and rheumatological manifestations [ 133 ]. The prevalence of sicca symptoms has been estimated to affect between 10% to 30% of HCV-infected patients [ 134 , 135 , 136 , 137 , 138 ]. On the other hand, less than 5% of patients with SS are HCV-positive [ 133 ].…”
Section: Diffuse Infiltrative Lymphocytosis Syndrome: Definition Amentioning
confidence: 99%
“…Some studies report that up to 50% of all HCV patients have chronic focal sialoadenitis [ 139 ]. As a result, sicca symptoms are common in this population, though usually less severe when compared to SS [ 137 , 140 , 141 ]. It remains unknown whether the virus causes a disease that mimics SS, or if HCV leads to the development of SS.…”
Section: Diffuse Infiltrative Lymphocytosis Syndrome: Definition Amentioning
confidence: 99%
“…A recent study on the prevalence of HBV infection in patients with SS (603 cases) in Spain showed a slight increase in the percentage of HBV infection in SS patients (HBsAg + 0.83%) compared to the population controls (HBsAg + 0.7%) 31 . Additionally, a study of SS patients from Taiwan (9,629 cases) infected with HBV showed that the HBV infection was more frequent in SS patients (4.3%) than in the healthy population (3.6%, 38,516 controls) 30 . Our data indicated that there is an increased incidence of HBV in SS patients carrying the A allele.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 350 million individuals worldwide infected with HBV, 33% reside in China 27 . Although there is accumulating evidence indicating that hepatitis C virus (HCV) infection contributes to the etiology of SS 28 , 29 , there is a limited number of reports regarding the nature of the association between SS and HBV infection 30 – 32 . Two large cohort studies have suggested that HBV infection might be more prevalent in patients with SS than in the general population 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%